The role of cuboidal ω precipitates on α precipitation in a Ti-20V alloy. (October 2016) - Zheng, Yufeng; Choudhuri, Deep; Alam, Talukder; Williams, Robert E.A.; Banerjee, Rajarshi; Fraser, Hamish L.
Abstract: The early stages of super-refined α phase precipitation, aided by the presence of precursory isothermal cuboidal ω precipitates, in a Ti-20V alloy, has been investigated by coupling conventional transmission electron microscopy (TEM), high resolution scanning transmission electron microscopy (HRSTEM), including energy dispersive spectroscopy (EDS), and atom probe tomography (APT). These complementary techniques, reveal for the first time, conclusive experimental evidence of nucleation of α precipitates at the ω/β interface and the attendant partitioning of elements. Graphical abstract: